Extreme oncoplasty: past, present and future - Vieira, René Aloisio da Costa; Paulinelli, Regis Resende; de Oliveira-Junior, Idam (Frontiers in Oncology, 2024)
Breast surgery has evolved from mastectomy to breast-conserving surgery (BCS).Breast oncoplastic surgery later emerged with the inclusion and development of techniques used in plastic surgery for breast neoplasms. Recently, a new paradigm has been considered for mastectomy candidates with large multifocal and multicentric tumours, designated extreme oncoplasty (EO), which has allowed new techniques to be applied to tumours that would have been ineligible for BCS before. There are few publications and no uniform descriptions grouping all the technical possibilities and new indications together. We performed this a review with the objective of evaluating the indications and surgeries performed in the EO context, representing a new perspective for BCS. We observed new indications as extensive microcalcifications, locally advanced breast carcinoma with partial response to chemotherapy, small to moderate-sized nonptotic central tumors and extreme ptosis. Small breasts are able for EO since the presence of ptosis. New surgeries are reported as disguised geometric compensation, perforators flaps, local/regional flaps, latissimus dorsi miniflap and partial breast amputation. It is important to decrease barriers to oncoplastic surgery if we want to increase the use of EO and BCS rates.